Analysis of the Interest of SMAN 10 Bandung City Students in Physics as the Basis of Modern Science - Fitrotul Uyun, Eka; Qeianu Rafly, Marzhal; Dwi Putra, Rizki Septianto; Andrian Immanuel, Sopaheluwakan (Jurnal Edusci, 2025)
This study aims to find out the interest of students in grades 11 and 12 of SMAN 10 Bandung City in physics subjects. Data collection was carried out using a questionnaire based on the Likert scale with a range of 1 to 10. The results of the study show that the majority of students have a fairly high interest. As many as 60 percent of students are on a scale of 7 to 10, which indicates a good interest in physics subjects. However, there were 12.5 percent of students had low interest, with scores on a scale of 1 to 4. In addition, about 17 percent of students are on a scale of 5 and 6, which shows a neutral attitude towards the subject. This result shows that there is great potential to improve the quality of physics learning. Groups of students with low interest need to get special attention through more interesting learning methods. Some strategies that can be carried out include the use of direct experiments, the application of physics concepts in daily life, and project-based activities. This effort is expected to be able to change students' views on physics to be more positive and relevant to their needs. This study concludes that applied physics learning has been effective for most students. However, a more innovative approach is still needed so that all students have a better interest in physics as an applicable and useful science.